Evaluation of the single yeast cell's adhesion to ito substrates with various surface energies via esem nanorobotic manipulation system - Yajing, Shen (Institute of Electrical and Electronics Engineers, 2011)
Cell-surface adhesion force is important for cell activities and the development of bio materials. In this paper, a method for in situ single cell (W303) adhesion force measurement was proposed based on nanorobotic manipulation system inside an environment scanning electron microscope (ESEM). An end effector was fabricated from a commercial atomic force microscope (AFM) cantilever by focused ion beam (FIB) etching. The spring constant of it was calibrated by nanomanipulation approach. Three kinds of hydrophilic and hydrophobic ITO plates were prepared by using VUV-irradiation and OTS coating techniques. The shear adhesion strength of the single yeast cell to each substrate was measured based on the deflection of the end effector. The results demonstrated that the cell adhesion force was larger under the wet condition in the ESEM environment than in the aqueous condition. It also showed that the cell adhesion force to hydrophilic surface was larger than that to the hydrophobic surface. Studies of single cell's adhesion on various plate surfaces and environments could give new insights into the tissue engineering and biological field.